2012
DOI: 10.4315/0362-028x.jfp-11-543
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Commercial and Pecan Shell-Extracted Liquid Smoke Agents as Natural Antimicrobials against Foodborne Pathogens

Abstract: Liquid smoke extracts have traditionally been used as flavoring agents, are known to possess antioxidant properties, and serve as natural alternatives to conventional antimicrobials. The antimicrobial efficacies of commercial liquid smoke samples may vary depending on their source and composition and the methods used to extract and concentrate the smoke. We investigated the MICs of eight commercial liquid smoke samples against Salmonella Enteritidis, Staphylococcus aureus, and Escherichia coli . The commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
1
21
0
4
Order By: Relevance
“…Two studies demonstrated that liquid smoke (LS), a product obtained from roasted or non-roasted pecan nutshell that is normally used as a flavoring agent, presented antimicrobial activity against foodborne pathogens (Escherichia, Salmonella and Staphylococcus). LS obtained with roasted pecan nutshell showed higher inhibition compared to non-roasted nutshells, probably due to the formation of Maillard compounds during roasting process (Van Loo et al, 2012). These authors also observed that LS extracts obtained with acetic acid showed higher inhibition than those obtained with methanol, while no inhibition was observed when water or hexane were used as extraction solvents.…”
Section: Biological Activity Of Pecan By-productsmentioning
confidence: 87%
“…Two studies demonstrated that liquid smoke (LS), a product obtained from roasted or non-roasted pecan nutshell that is normally used as a flavoring agent, presented antimicrobial activity against foodborne pathogens (Escherichia, Salmonella and Staphylococcus). LS obtained with roasted pecan nutshell showed higher inhibition compared to non-roasted nutshells, probably due to the formation of Maillard compounds during roasting process (Van Loo et al, 2012). These authors also observed that LS extracts obtained with acetic acid showed higher inhibition than those obtained with methanol, while no inhibition was observed when water or hexane were used as extraction solvents.…”
Section: Biological Activity Of Pecan By-productsmentioning
confidence: 87%
“…Liquid smoke can be applied directly to or incorporated into a product. Researchers have evaluated the antimicrobial properties of liquid smoke against a wide range of foodborne pathogens, including Listeria monocytogenes, Salmonella, Yersina enterocolitica, Staphylococcus aureus, and Escherichia coli [124][125][126]. Molds inhibition, such as of Aspergillus parasiticus, Penicillium camemberti, and Penicillium roqueforti, linked to cheese deterioration has also been demonstrated [127].…”
Section: Food Preservative Applications Of Prosopis Plantsmentioning
confidence: 99%
“…Thus, understanding carbonyl compounds, and acids concentrations, and pH of a liquid smoke product is essential to ensure proper food preservation and appropriate sensory characteristics. The minimum inhibitory concentration (MIC) of commercial liquid smoke samples against E. coli, Salmonella and S. aureus was determined [126]. Commercial mesquite liquid smoke concentrated extracts exhibited low %MIC's of less than 1% for each pathogen.…”
Section: Food Preservative Applications Of Prosopis Plantsmentioning
confidence: 99%
“…Essential oil fractions of several herbs and spices are widely reported in literature to have food preservative properties and antimicrobial effects on food pathogens (Friedman and others ; Olasupo and others ); however, only a few studies indicate the utilization of natural antimicrobials extracted from organically grown plants or plant products. We recently reported the efficacies of natural antimicrobials extracted from organic pecan shells on inhibiting the growth of various food pathogens (Van Loo and others ). Fasina and Littlefield () completed an exhaustive characterization of the products produced during the thermal decomposition of pecan shells.…”
Section: Introductionmentioning
confidence: 99%